Development of Problem-Based Learning Worksheets Integrated with Think–Pair–Share to Enhance Students’ Critical Thinking Skills on Reaction Rate Topics - Ameiliana Nur Azizah; Harjono Harjono (Jurnal Inovasi Pendidikan Kimia, 2025)
This study aimed to examine the feasibility, effectiveness, and practicality of a reaction rate worksheet based on Problem-Based Learning (PBL) integrated with the Think–Pair–Share (TPS) strategy to enhance students’ critical thinking skills. This research employed a Research and Development (R&D) approach using the 4-D development model, consisting of the define, design, development, and dissemination stages. The developed worksheet was evaluated in terms of feasibility through expert validation, effectiveness through learning outcomes, and student responses. The feasibility results indicated that the worksheet was rated as very feasible, with material expert validation reaching 89.81% and media expert validation achieving 95.83%. In addition, the readability test yielded a score of 89.70%, which also fell into the very feasible category. The effectiveness of the worksheet was determined through a t-test analysis, showing that the calculated t-value exceeded the t-table value, indicating that the use of the worksheet effectively improved students’ critical thinking skills. Classical learning completeness in the experimental class reached 80.56% (categorized as proper), while the control class achieved 44.44% (categorized as quite proper). Furthermore, the critical thinking score of the experimental class reached 82.43% (very critical), compared to 72.09% (critical) in the control class. Observational results also revealed that students in the experimental class demonstrated higher critical thinking abilities than those in the control class. Student responses to the worksheet were highly positive, with an average score of 85.81%, categorized as very good. Overall, the findings indicate that the PBL-based worksheet integrated with Think–Pair–Share is feasible, effective, and well-received as an instructional material for training students’ critical thinking skills.